Awareness, perception & practices towards blood donation among students in UiTM Kampus Bertam / Muhammad Nazwan Ahmad Bazar, Nursuraya Hamid and Nur Afrina Affendi - Ahmad Bazar, Muhammad Nazwan; Hamid, Nursuraya; Affendi, Nur Afrina (2023)
This report demonstrates on the chosen project, Awareness, Perception and Knowledge Towards Blood Donation Among Students in Universiti Teknologi MARA (UiTM) Kampus Bertam. From this project, students are expected to develop their awareness and knowledge of blood donation that plays an important role in keeping the blood supply or stocks in a stable condition. However, students’ problem is that they are unable to obtain up-to-date information on events or programmes such as a blood donation campaign that is taking place within the university. Thus, it shows students lack of awareness that can lead to incomprehension on how blood donation is important, works and procedures itself. The methodology used in this project to collect student’s data in this project is a quantitative method such as questionnaires in which a survey was conducted to reflect the awareness, knowledge, and practice of students towards blood donation. The results of this project were collected from the response from students in UiTM Kampus Bertam. 85 students were taking part in the survey conducted.